Inhibition of neurogenic and thromboxane A2‐induced human prostate smooth muscle contraction by the integrin α2β1 inhibitor BTT‐3033 and the integrin‐linked kinase inhibitor Cpd22. Issue 11 (25th May 2020) - Li, Bingsheng; Wang, Xiaolong; Wang, Ruixiao; Rutz, Beata; Ciotkowska, Anna; Gratzke, Christian; Herlemann, Annika; Spek, Annabel; Tamalunas, Alexander; Waidelich, Raphaela; Stief, Christian G.; Hennenberg, Martin
Abstract: Introduction: Prostate smooth muscle contraction is critical for etiology and treatment of lower urinary tract symptoms in benign prostatic hyperplasia (BPH). Integrins connect the cytoskeleton to membranes and cells to extracellular matrix, what is essential for force generation in smooth muscle contraction. Integrins are composed of different subunits and may cooperate with integrin‐linked kinase (ILK). Here, we examined effects of inhibitors for different integrin heterodimers and ILK on contraction of human prostate tissues. Methods: Prostate tissues were obtained from radical prostatectomy. Integrins and ILK were detected by Western blot, real‐time polymerase chain reaction (RT‐PCR), and double fluorescence staining. Smooth muscle contractions of prostate strips were studied in an organ bath. Contractions were compared after application of solvent (controls), the ILK inhibitor Cpd22 ( N ‐methyl‐3‐(1‐(4‐(piperazin‐1‐yl)phenyl)‐5‐(4'‐(trifluoromethyl)‐[1, 1'‐biphenyl]‐4‐yl)‐1H‐pyrazol‐3‐yl)propanamide), the integrin α2β1 inhibitor BTT‐3033 (1‐(4‐fluorophenyl)‐ N ‐methyl‐ N ‐[4[[(phenylamino)carbonyl]amino]phenyl]‐1H‐pyrazole‐4‐sulfonamide), or the integrin α4β1/α9β1 inhibitor BOP ( N ‐(benzenesulfonyl)‐ l ‐prolyl‐ l ‐O‐(1‐pyrrolidinylcarbonyl)tyrosine sodium salt). Results: Western blot analyses of prostate tissues using antibodies raised against integrins α2b, α4, α9, β1, and ILK revealed bands matching the expected sizes of corresponding antigens. Expression of integrins and ILK was confirmed by RT‐PCR. Individual variations of expression levels occurred independently from divergent degree of BPH, reflected by different contents of prostate‐specific antigen. Double fluorescence staining of prostate sections using antibodies raised against integrins α2 and β1, or against ILK resulted in immunoreactivity colocalizing with calponin, suggesting localization in prostate smooth muscle cells. Electric field stimulation (EFS) induced frequency‐dependent contractions, which were inhibited by Cpd22 (3 µM) and BTT‐3033 (1 µM) (inhibition around 37% by Cpd22 and 46% by BTT‐3033 at 32 Hz). The thromboxane A2 analog U46619‐induced concentration‐dependent contractions, which were inhibited by Cpd22 and BTT‐3033 (around 67% by Cpd22 and 39% by BTT‐3033 at 30 µM U46619). Endothelin‐1 induced concentration‐dependent contractions, which were not affected by Cpd22 or BTT‐3033. Noradrenaline and the α1 ‐adrenergic agonists methoxamine and phenylephrine‐induced concentration‐dependent contractions, which were not or very slightly inhibited by Cpd22 and BTT‐3033. BOP did not change EFS‐ or agonist‐induced contraction. Conclusions: Integrin α2β1 and ILK inhibitors inhibit neurogenic and thromboxane A2 ‐induced prostate smooth muscle contraction in human BPH. A role for these targets for prostate smooth muscle contraction may appear possible.